EVOLUTION OF THE PHENOMENON OF WAR - PANKOWSKA Edyta (2018)
The aim of this article is to analyze the evolution of wars over the centuries, and the reasons for their occurrence. The author raises issues forming the basis of thinking about armed conflicts from the perspective of researchers, state governments, the world of business and ordinary citizens. A number of selected concepts of warfare by the most important authors of various eras were presented. Investigation of factors having influence on armed conflicts also contributed to the attempt to determine the impact of such factors as technological progress, geographical, political, social and other conditions, causing or reducing the likelihood of war. In addition, four schools of warfare were presented regarding the sources of advantage between the parties of the conflict. An analysis of a number of cases, examples and views allowed specifying the author’s own view, leaning towards a rationalistic theorem, propagated inter alia by J.D. Fearon. According to him, armed conflicts mainly break out when they are profitable or more favorable than other, peaceful alternatives. An important difference between the “old” and “new” wars is primarily the asymmetry of conflicts resulting not only from the technological, economic or social disproportion, but rather the possibility of remote impact, as some world powers do. This allows for a cheaper war with a limited use of military force.